2018 IEEE 31st International Symposium on Computer-Based Medical Systems (CBMS) 2018
DOI: 10.1109/cbms.2018.00048
|View full text |Cite
|
Sign up to set email alerts
|

Blink-Based Estimation of Suturing Task Workload and Expertise in Microsurgery

Abstract: Artikkelit ja abstraktit tieteellisissä konferenssijulkaisuissa © IEEE All rights reservedAbstract-Eye-hand coordination is a central skill in microsurgery. To develop efficacious microsurgical training environments to support development of eye-hand coordination, it is important to understand the workload associated with visuomotor tasks in microsurgery. We embedded an eye-tracker to a surgical microscope and collected eye-blink data of 10 participants during a microsuture training task. Blink-rate was shown … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…In another study, the blink rate was shown to drop to low levels compared to a resting-state rate and be sensitive to the phases of microsurgical suture [164]. In a driving scenario in [163], the eye tracker showed increasing blink rates along with the parallel increase in the difficulty of a -parallel with driving-performed secondary task.…”
Section: Metrics Related To Cognitive Workloadmentioning
confidence: 92%
“…In another study, the blink rate was shown to drop to low levels compared to a resting-state rate and be sensitive to the phases of microsurgical suture [164]. In a driving scenario in [163], the eye tracker showed increasing blink rates along with the parallel increase in the difficulty of a -parallel with driving-performed secondary task.…”
Section: Metrics Related To Cognitive Workloadmentioning
confidence: 92%
“…Lower blink frequency range was associated with higher NASA-TLX ratings during simulated laparoscopic tasks (Zheng et al, 2012). In addition, blink rate was higher for experts than novices during the cutting phase of simulated microsurgery although it did not vary for any of the other phases (Bednarik, Koskinen, Vrzakova, Bartczak, & Elomaa, 2018). However, these studies were limited to basic skills tasks and laparoscopic techniques.…”
Section: Introductionmentioning
confidence: 99%
“…With a custom eye tracker embedded into a surgical microscope, we recorded the blinks and pupil dilations of novice and expert microsurgeons as they performed a set of microsurgical training sutures. In our previous research, 28,29 we found that novices estimated the suturing task to be significantly more demanding than experts and that there are differences in pupil dilations and blink rates between these 2 groups. Here, we extend this research by studying the combined applicability of pupil dilation and blink rate to classify expertise at suture-and segment-level features.…”
Section: Introductionmentioning
confidence: 77%